Regulation of PCNA–protein interactions for genome stability - Mailand, Niels; Gibbs-Seymour, Ian; Bekker-Jensen, Simon (Nature reviews. Molecular cell biology, 2013)
Key Points The sliding clamp proliferating cell nuclear antigen (PCNA) has a crucial role as a processivity factor for DNA replication in eukaryotic cells. PCNA provides a central platform for coordinating many replication-associated processes, such as DNA damage repair or bypass, chromatin establishment and sister chromatid cohesion. A large number of cellular proteins compete for binding to a common surface on PCNA, necessitating tight, multilayered regulatory mechanisms that enable a fine-tuned interplay between PCNA and appropriate partner proteins at different stages of DNA replication and associated processes. The PCNA-interacting protein (PIP) box, which is present in numerous proteins, is an important determinant for PCNA binding. Relative PCNA-binding affinities of PIP boxes establish a basic hierarchy of PCNA interactions. Regulatory mechanisms controlling and modulating PCNA–protein interactions include post-translational modifications of PCNA and its associated proteins, accessory factors regulating PCNA–protein interactions and selective proteasome-dependent degradation of PCNA-bound proteins. Mono- and polyubiquitylation of PCNA have key roles in enabling bypass of replication-associated DNA damage via translesion DNA synthesis and template switching, respectively. Many new PCNA-binding proteins have been identified and characterized in recent years, broadening our understanding of the organization and regulation of PCNA-dependent processes underlying genome stability maintenance at the replication fork. The proliferating cell nuclear antigen (PCNA) processivity factor provides a central regulatory platform during DNA replication and associated processes, including DNA damage repair. The interaction of PCNA with many cellular proteins is key to this function and is subject to tight, multilayered control. Proliferating cell nuclear antigen (PCNA) has a central role in promoting faithful DNA replication, providing a molecular platform that facilitates the myriad protein–protein and protein–DNA interactions that occur at the replication fork. Numerous PCNA-associated proteins compete for binding to a common surface on PCNA; hence these interactions need to be tightly regulated and coordinated to ensure proper chromosome replication and integrity. Control of PCNA–protein interactions is multilayered and involves post-translational modifications, in particular ubiquitylation, accessory factors and regulated degradation of PCNA-associated proteins. This regulatory framework allows cells to maintain a fine-tuned balance between replication fidelity and processivity in response to DNA damage.